Seismic safety evaluation of electric power supply at urban level. - Nuti, Camillo (Earthquake engineering & structural dynamics.)
In past works the authors set up a refined model for electric power networks under earthquake action. The procedure models the fragility of components with respect to earthquake action, the complex behaviour of the stations and the network, the power flow, the network capability to feed the nodes in a damaged condition, the earthquake damage on the territory, the need to deliver electric power to the municipalities where most damage has occurred. In later works the method was improved towards design goals: nonetheless complexity of the network seismic behaviour, a procedure to maximize safety of selected nodes and minimize economic expenses was constructed, allowing identification of which components, within each station, had to be upgraded to obtain the maximum economic convenience. The procedure was programmed within the ASK4ELP computer code (National Information Service for Earthquake Engineering, University of California, Berkeley, U.S.A., 1999) using late 1990s state-of-the-art knowledge for both the earthquake and the structural behaviour models. Recently the method has gone through a thorough updating, partially still in progress. Among the results, it is now more clear how important is a correct soil geotechnical model to predict the system response and safety. This paper presents, together with a short summary of the ASK4ELP procedure, these latest advancements and results and shows, through a real example, the sensitivity of the predicted safety to soil modelling.